Catching-up with the 'locomotive': a simple theory - Raouf Boucekkine; Benteng Zou (Bielefeld University, Institute of Mathematical Economics (IMW), 2010)
This paper extends the standard neoclassical model by considering a technology sector through which an economy with limited human capital attempts to catch up with a given 'locomotive' pushing exogenously technical progress. In periods of technological stagnation, economies close enough to the frontier may find it optimal to not catch up, which reinforces worldwide technological sclerosis. Under sustainable technological growth, all the other economies will sooner or later engage in imitation. Such a phase of technology adoption may be delayed depending on certain deep characteristics of the followers.
urn:nbn:de:hbz:361-16609
Keywords: 330; Wirtschaftswachstum; Internationale Wirtschaftsbeziehungen; Technischer Fortschritt; Konjunkturzusammenhang; Imitationswettbewerb; Theorie